Analisis Efektivitas Program Makan Bergizi Gratis di SMP Kecamatan Gunungpati Kota Semarang - Sri Wahyuni Ningsih; Mirza Fathan Fuadi; Luluk Hilda Kusumarini (Malahayati Nursing Journal, 2026)
ABSTRACT Nutritional problems in school-aged children are a health issue that directly impacts the quality of education and human resource development in the future. Adolescents, especially junior high school students (SMP), require adequate and balanced nutritional intake to support growth and development, concentration in learning, and endurance. The Free Nutritious Meal Program (MBG) is a program introduced by the Indonesian government in 2025 to address nutritional issues, reduce stunting rates, and improve the quality of education. This study aims to evaluate the effectiveness of the MBG program at the junior high school level (SMP) in Gunungpati District, Semarang City. The research method used descriptive qualitative. Data were obtained from in-depth and systematic interviews with informants including principals, teachers, and junior high school students who received the MBG program from SPPG Bina Bangsa Semarang, as well as field observations. The sample of this study was 18 people from three junior high schools in Gunungpati District, Semarang City, namely SMPN 19 Semarang, SMPN 41 Semarang, and MTs Al-Hidayah Semarang. To maintain the validity of the data, the researcher used triangulation techniques. Research results indicate that the MBG program has a positive impact on student nutritional improvement, focus, and attendance. However, several challenges remain in managing the MBG program, including distribution times, food quality, and differences in student understanding of nutrition. Regular evaluation and quality monitoring of the MBG program are needed to optimize the program. With sustainable management, the MBG program has the potential to support the development of a healthy and high-quality young generation. Keywords: Free Nutritious Meals (MBG), Adolescent Nutrition, MBG Effectiveness.  ABSTRAK Masalah gizi pada anak usia sekolah merupakan salah satu masalah kesehatan yang berdampak langsung terhadap kualitas pendidikan dan pembangunan sumber daya manusia di masa depan. Anak-anak usia remaja, khususnya siswa Sekolah Menengah Pertama (SMP), membutuhkan asupan gizi yang cukup dan seimbang untuk mendukung proses tumbuh kembang, konsentrasi belajar dan daya tahan tubuh. Program Makan Bergizi Gratis (MBG) adalah sebuah program yang diperkenalkan oleh pemerintah Indonesia pada tahun 2025 untuk mengatasi permasalahan gizi, menurunkan angka stunting, dan meningkatkan mutu pendidikan. Penelitian ini memiliki tujuan untuk melakukan evaluasi efektifitas program MBG di tingkat Sekolah Menengah Pertama (SMP) Kecamatan Gunungpati Kota Semarang. Metode penelitian menggunakan kualitatif deskriptif. Data dihasilkan dari wawancara mendalam dan sistematis kepada kepala sekolah,  guru, dan siswa SMP yang menerima program MBG dari SPPG Bina Bangsa Semarang serta observasi di lapangan. Sampel dari penelitian ini berjumlah 18 orang yang berasal dari tiga sekolah menengah pertama di Kecamatan Gunungpati Kota Semarang yaitu SMPN 19 Semarang, SMPN 41 Semarang dan MTs Al-Hidayah Semarang. Dalam menjaga keabsahan data, peneliti menggunakan teknik triangulasi. Hasil Penelitian menunjukkan bahwa MBG berdampak positif pada perbaikan gizi, fokus, dan kehadiran siswa. Namun dalam pengelolaan MBG masih memiliki beberapa kendala seperti waktu pendistribusian, mutu makanan dan perbedaan pemahaman gizi pada siswa. Diperlukan evaluasi rutin serta pengawasan kualitas MBG agar program lebih optimal. Dengan pengelolaan yang berkelanjutan, program MBG berpotensi mendukung terbentuknya generasi muda yang sehat dan berkualitas. Kata Kunci: Makan Bergizi Gratis (MBG), Gizi Remaja, Efektivitas MBG.